Operating conditions of electric energy storage system in DC traction power supply for single-track sections of railways - V. L. Nezevak (Вестник Научно-исследовательского института железнодорожного транспорта, 2021)
Considered are the issues of using electric energy storage system in the traction power supply of direct current of a single-track section. An overview of the main directions of domestic and foreign research in the field of using these systems to increase the capacity and energy efficiency of power supply systems is given. Modeling the operation of energy storage system in traction power supply is based on the calculation of load graphs within the boundaries of inter-substation zones, formed depending on the conditions for the passage of trains and traction load on the railway section. The main provisions of the method for choosing locations and determining the parameters of energy storage system in traction power supply are considered. On the example of one of the inter-substation zones of the Sverdlovsk railway, the influence of the power of the active sectioning station on the increase in the minimum voltage level at the pantograph of the electric rolling stock is shown. The graphs of the degree of charge and the corresponding frequency distributions are given, which make it possible to evaluate the operating conditions of the electric energy storage system depending on the conditions for the formation of the traction load, as well as the graphs of the load of the electric energy storage system and the corresponding charging characteristics for the operating conditions at the sectioning post. On the example of the section under consideration, the dependence of the discharge depth of the electric energy storage system on the nominal energy intensity is shown. Based on the results of calculations, an evaluation was made of the options for passing train batches in the even and odd direction in comparison with the schedule of the performed train operation. The range of variation of the nominal values of power and energy intensity of the electric energy storage system is obtained. Comparison of the accumulation system parameters for single- and double-track sections of railways, including those with a predominance of passenger traffic, is carried out.